Karakteristik Pengeringan Jahe Merah (Zingiber officinale Var. Rubrum) Menggunakan Alat Pengering Tipe Kubah: Karakteristik Pengeringan Jahe Merah (Zingiber officinale Var. Rubrum) Menggunakan Alat Pengering Tipe Kubah - Ireine Longdong; Dedie Tooy; Ruland A. Rantung; Keisya Ransun; Herry Pinatik; Denny Saroinsong (Jurnal Teknologi Pertanian (Agricultural Technology Journal), 2025)
This study aims to examine the drying characteristics of red ginger (Zingiber officinale var. rubrum) using a dome-type dryer with three variations in slice thickness, namely 0.5 cm, 1 cm, and 1.5 cm. The parameters analyzed included drying temperature, relative humidity (RH), material moisture content, and drying rate over time. The research was carried out at the Biosystems Engineering Laboratory, Faculty of Agriculture, Sam Ratulangi University using observational methods. The research material is in the form of red ginger that is sorted, washed, and sliced according to treatment. The drying process is carried out by placing the sample on the drying tray, then observation is made of the initial moisture content using the oven method, temperature and humidity inside and outside the dryer, light intensity, and weight loss of the material every 60 minutes. The results showed that the drying temperature during the first to the sixth day ranged from 27.3°C to 50°C. The relative humidity of the drying chamber is in the range of 35% to 61%. The initial moisture content of the entire slice treatment was 80.39%. The final moisture content obtained in 0.5 cm slices was 10.37%, 10.51 cm slices, and 1.5 cm slices were 10.48%. The time needed to achieve a moisture content of about 10% is different in each treatment, namely 4 days 33 hours for 0.5 cm slices, 5 days 44 hours for 1 cm slices, and 6 days 49 hours for 1.5 cm slices. The conclusion of this study shows that the dome-type dryer is effective in reducing the moisture content of red ginger until it reaches storage standards. In addition, the thickness of the slices has been shown to affect the rate and duration of drying. These results can be used as a basis for the development of small-scale ginger drying technology in the post-harvest process.